Protein analysis and purification : Benchtop techniques. - Rosenberg, Ian M., ....- (Boston : Birkhäuser, 2005)
This comprehensive, practical, and user-friendly manual is designed to be a practical progression of experimental protocols that an inexperienced investigator may follow when embarking on a biochemical or biotechnology project. It will also appeal to experienced researches and graduate students as a benchtop handbook which, without sacrificing scientific concepts, maintains the spirit of experimentation. Written for: Biochemists/graduate students, molecular biologists/graduate students, cell biologists/graduate students